2013
DOI: 10.1590/s0104-11692013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the process of living as signified by myocardial revascularization surgery patients

Abstract: Objective: To understand the meanings for the process of living, for patients undergoing myocardial revascularization surgery, and to construct an explanatory theoretical model. Method: Grounded Theory was used, with data collection undertaken between October 2010 and May 2012, in a health institution which specializes in cardiac surgery, located in the south of Brazil. Thirty-three subjects were interviewed (patients, health care professionals and family members), distributed in four sample groups. Result: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
1
8
0
6
Order By: Relevance
“…Analogous data were observed in the study of Erdmann, Lanzoni, Callegaro, Baggio and Koerich (2013), which observed that the postsurgical condition can accentuate situations of family conflict, mainly regarding the family's demands in relation to changes in the patient's lifestyle.…”
Section: Relationships In the Context Of The Familysupporting
confidence: 72%
See 1 more Smart Citation
“…Analogous data were observed in the study of Erdmann, Lanzoni, Callegaro, Baggio and Koerich (2013), which observed that the postsurgical condition can accentuate situations of family conflict, mainly regarding the family's demands in relation to changes in the patient's lifestyle.…”
Section: Relationships In the Context Of The Familysupporting
confidence: 72%
“…As a resource for understanding this panorama, it is appropriate to mention that, of the 12 interviewees, six were not undertaking work activities at the time of the interview, due to the surgical process itself or to the phase of their life cycle the participants were experiencing (two were retired due to length of service). The difficulty in the scenario of professional life after surgery is a context corroborated by other studies, according to which restrictions in relation to carrying out work activities after cardiac surgery entail emotional and financial repercussions for the patients (Callegaro, Koerich, Lanzoni, Baggio, & Erdmann, 2012;Erdmann et al, 2013).…”
Section: Relations In the Context Of The Workmentioning
confidence: 70%
“…In Brazil, research that considers hope of chronic patients and their relationship with the clinic are relatively recent, keeping in mind that the authors who translated and validated the scale stated that until 2005 there was no instrument available in Portuguese for such (9) . However, the hope construct has emerged in qualitative research to understand the meanings and factors that influence the process of going through cardiac revascularization surgery for patients, families and healthcare professionals (20)(21)(22)(23) . In these studies, spirituality is referred as important in the participation in the surgical experience, since patients can share their anguishes with God and have, in faith, the hope of achieving good results after surgery (20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the hope construct has emerged in qualitative research to understand the meanings and factors that influence the process of going through cardiac revascularization surgery for patients, families and healthcare professionals (20)(21)(22)(23) . In these studies, spirituality is referred as important in the participation in the surgical experience, since patients can share their anguishes with God and have, in faith, the hope of achieving good results after surgery (20)(21)(22)(23) . Lastly, although the relation between hope, faith and religiosity and the expectation about the surgery is frequent, patients can refer to it without making such correlation, just by knowing that the prognosis without surgery would be worse, despite the arising risks (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Paralelamente, nessa amostra, Apoio da família, dos amigos e de outros também se sobressaiu entre os relatos (42,9 %), o que corrobora resultados da literatura (32). Quanto ao domínio Resolução de problemas, ao observar seu destaque no IEC, compreendeu-se que, para essa amostra, a realização do procedimento cirúrgico parece ter significado de resolução da obstrução coronariana, o que corrobora resultados da literatura (33).…”
Section: Discussionunclassified